Effectiveness of a pragmatic school-based universal resilience intervention in reducing tobacco, alcohol and illicit substance use in a population of adolescents: cluster-randomised controlled trial. Issue 8 (18th August 2017) - Hodder, Rebecca Kate; Freund, Megan; Bowman, Jenny; Wolfenden, Luke; Campbell, Elizabeth; Dray, Julia; Lecathelinais, Christophe; Oldmeadow, Christopher; Attia, John; Wiggers, John
Abstract : Objectives: Initiation of tobacco, alcohol and illicit substance use typically occurs during adolescence, with the school setting recommended to reduce adolescent substance use. Strengthening individual (eg, problem solving) and environmental (eg, caring relationships at school) resilience protective factors of adolescents has been suggested as a strategy for reducing substance use by adolescents; however, few studies have examined this potential. A study was conducted to investigate the effectiveness of a pragmatic school-based universal 'resilience' intervention in reducing the prevalence of tobacco, alcohol and illicit substance use, and increasing the individual and environmental protective factors of students. Design: A cluster-randomised controlled trial. Setting: Thirty-two Australian secondary schools (20 intervention; 12 control). Participants: Cohort of grade 7 students followed-up in grade 10 (2014; aged 15–16 years). Intervention: A pragmatic intervention involving school staff selection and implementation of available programmes and resources targeting individual and environmental 'resilience' protective factors for all grade 7–10 students was implemented in schools (2012–2014). School staff were provided implementation support. Measurements: An online survey collected baseline and follow-up data for primary outcomes: tobacco (ever, recent) and alcohol (ever, recent, 'risk') use, and secondary outcomes: marijuana and other illicit substance use, and individual (six-factor subscales, aggregate) and environmental (three-factor subscales, aggregate) protective factor scores. Generalised and linear mixed models examined follow-up differences between groups. Results: Follow-up data from 2105 students (intervention=1261; control=844; 69% of baseline cohort) were analysed. No significant differences were found between intervention and control students for any primary (ever tobacco: OR 1.25, 95% CI 0.92 to 1.68, p=0.14; recent tobacco: OR 1.39, 95% CI 0.84 to 2.31, p=0.19; recent ever alcohol: OR 1.11, 95% CI 0.83 to 1.48, p=0.46; alcohol: OR 1.13, 95% CI 0.78 to 1.62, p=0.51; 'risk' alcohol: OR 0.98, 95% CI 0.70 to 1.36, p=0.89) or secondary outcomes (marijuana: OR 1.12, 95% CI 0.74 to 1.68, p=0.57; other illicit substance: OR 1.19, 95% CI 0.67 to 2.10, p=0.54; individual protective factors: MD=0, 95% CI −0.07 to 0.06, p=0.89; environmental protective factors: MD: −0.02, 95% CI −0.09 to 0.06, p=0.65). Conclusions: The universally implemented pragmatic school-based intervention was not effective in reducing the prevalence of tobacco, alcohol or illicit substance use, or in increasing the protective factors of students. Trial registration: Australia and New Zealand Clinical Trials Register reference: ACTRN12611000606987